The effect of job insecurity on knowledge hiding behavior: The mediation of psychological safety and the moderation of servant leadership - Jeong, Jeeyoon; Kim, Byung-Jik; Lee, Julak (Frontiers in Public Health, 2023)
As the global economy deteriorates because of the great shocks such as COVID-19 pandemic and wars among nations, the business environment is suffered from uncertainty and risk. To deal with it, several firms have attempted to maximize its efficiency via downsizing and restructuring to diminish costs. Thus, the degree of anxiety is increased among employees who worry about the loss of their job. The current research hypothesizes that job insecurity increases employees' knowledge hiding behavior by diminishing the degree of their psychological safety. In other words, psychological safety functions as the underlying process (i.e., mediator) in the job insecurity-knowledge hiding behavior link. Furthermore, this paper tries to examine the boundary condition of how to decrease the detrimental influence of job insecurity, focusing on the moderating effect of servant leadership. Utilizing a 3-wave time-lagged data from 365 Korean employees, we empirically demonstrated that employees who perceive job insecurity are less likely to perceive psychological safety, eventually increasing their knowledge hiding behavior. We also found that servant leadership functions as a positive moderator which buffers the negative impact of job insecurity on psychological safety. Theoretical and practical contributions are described.